Do clinical characteristics and outcome in nonagenarians with a hip fracture differ from younger patients?. Issue 1 (11th June 2012) - Vochteloo, Anne JH; Borger van der Burg, Boudewijn LS; Tuinebreijer, Wim E; de Vries, Mark R; Niggebrugge, Arthur HP; Bloem, Rolf M; Maier, Andrea B; Nelissen, Rob GHH; Pilot, Peter
<x xml:space="preserve">Abstract</x> Aim: To compare clinical characteristics and outcome of nonagenarian hip fracture patients with younger patients aged 65–89 years. Methods: This was a cohort follow‐up study of admissions for a hip fracture between 2005–2010 (mean follow up of 3.5 years) in two teaching hospitals in the Netherlands; 230 nonagenarians and 1014 patients aged 65–89 years were included. Clinical characteristics, adverse events, mobility and mortality were compared. Results: Nonagenarians were more likely to be female and anemic (both P < 0.001), and had more trochanteric fractures (P = 0.005). The number of American Society of Anesthesiologists III/VI classified patients did not differ between the two groups. During the hospital stay, adverse events were more frequently observed in nonagenarians compared with younger patients (P < 0.001). The length of stay was significantly longer in nonagenarians (P < 0.001), and the 90‐day readmission rate was similar. Absolute mortality was higher in nonagenarians (P < 0.001), excess mortality, however, was comparable. Before admission, 40.0% of the nonagenarians lived in their own home, and 40.9% had returned 3 months postfracture. The rate of returning to their own home was lower compared with younger patients (P < 0.001). Prefracture mobility was worse in nonagenarians compared with the younger group, but 3 months after discharge, the number of patients that regained prefracture mobility was comparable in both age groups. Conclusions: Nonagenarian hip fracture patients differ significantly from younger patients aged 65–89 years with respect to clinical characteristics and long‐term outcome. However, almost half of the nonagenarians returned to their own home and more than half regained their prefracture level of mobility. Given these findings, prevention strategies for hip fracture and adverse events during hospital stay that focus particularly on frail nonagenarians are highly recommended. Geriatr Gerontol Int 2013; 13: 190–197.